2006
DOI: 10.1002/app.23299
|View full text |Cite
|
Sign up to set email alerts
|

High temperature zone‐drawing of nylon 66 microfiber prepared by CO2 laser‐thinning

Abstract: ABSTRACT:A high temperature zone-drawing method was applied to a nylon 66 microfiber, obtained by using CO 2 laser-thinning, to develop its mechanical properties. The microfiber used for the high temperature zone-drawing was prepared by winding at 150 m min Ϫ1 the microfiber obtained by irradiating the laser at 4.0 W cm Ϫ2 to an original fiber with a diameter of 50 m, and had a diameter of 9.6 m and a birefringence of 0.019. The high temperature zonedrawing was carried out in two steps; the first drawing was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…It is well known that the molecular weight decreases by the thermal degradation occurred during the melt spinning. In the previous study,18 to examine whether the thermal degradation during the CO 2 laser‐irradiating occurred or not, the GPC measurements were carried out for the nylon 66 microfiber obtained by the CO 2 laser‐thinning. The results implied that molecular weight of the nylon 66 did not change before and after the laser irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the molecular weight decreases by the thermal degradation occurred during the melt spinning. In the previous study,18 to examine whether the thermal degradation during the CO 2 laser‐irradiating occurred or not, the GPC measurements were carried out for the nylon 66 microfiber obtained by the CO 2 laser‐thinning. The results implied that molecular weight of the nylon 66 did not change before and after the laser irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…A carbon dioxide (CO 2 ) laser‐thinning method developed by us could easily produce microfibers by irradiating a continuous‐wave CO 2 laser to fibers, such as poly(ethylene terephthalate) (PET),16 nylon 6,17 nylon 66,18 i‐polypropylene,19 poly( L ‐lactic acid) (PLLA),20, 21 and poly(ethylene ‐2,6‐ naphthalate) (PEN)22 fibers without highly skilled techniques. The microfiber obtained by winding on a spool in the winding speed range of 100–2500 m min −1 was monofilament microfiber with a uniform diameter.…”
Section: Introductionmentioning
confidence: 99%
“…SEM showed that the laser‐thinned (LT) microfibers had smooth surfaces not roughened by laser ablation, which were uniform in diameter. The change in the molecular weight during the CO 2 laser‐thinning hardly occurred as compared with its melt spinning 11…”
Section: Introductionmentioning
confidence: 99%
“…This method was previously applied to various polymers, such as PET and nylon 6 etc, to develop their mechanical properties12–16 and was suitable for improving the mechanical properties of fibers and films. The zone‐drawing and zone‐annealing method was also applied to the PET17 and nylon 6611 microfibers obtained by CO 2 laser‐thinning to develop their mechanical properties, and then high‐modulus and high‐strength microfibers were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…One approach is to heat the spinline by hot air or laser, such as in melt blowing and melt spinning with online laser heating. [4][5][6] With the increase of spinline temperature, the fibers tend to be attenuated more and usually finer fibers can be achieved. However, the fibers created from melt blowing are typically discontinuous with short fiber length.…”
mentioning
confidence: 99%